Hungry for peace: international security, humanitarian assistance, and social change in North Korea - Smith, Hazel (Washington, DC: United States Institute of Peace Press, 2005)
Smith describes the famine that devastated the country in the 1990s and the international rescue program that Pyongyang requested and received. Together, the famine and the humanitarian response have wrought subtle but profound changes in North Korea's economy, society, and security outlook. Smith argues that the regime has been prodded into accepting some international norms, allowed markets to develop, and has included some human security concerns alongside military-political interests in its negotiations with the West.
Includes bibliographical references (p. 235-318) and index.
Keywords: Humanitarian assistance -- Korea (North); Famines -- Korea (North); Korea (North) -- Politics and government; Korea (North) -- Foreign relations